2021
DOI: 10.3389/fcell.2020.618598
|View full text |Cite
|
Sign up to set email alerts
|

Secreted Phosphoprotein 1 Expression in Retinal Mononuclear Phagocytes Links Murine to Human Choroidal Neovascularization

Abstract: Age-related macular degeneration (AMD) represents the most common cause of blindness in the elderly in the Western world. An impairment of the outer blood-retina barrier and a localized inflammatory microenvironment cause sprouting of choroidal neovascular membranes (CNV) in neovascular AMD that are in intimate contact with surrounding myeloid cells, such as retinal microglia, and ultimately lead to visual impairment. The discovery of novel target molecules to interfere with angiogenesis and inflammation is vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 56 publications
0
24
0
1
Order By: Relevance
“…This suggests that Irf8 -deficient MG are functionally sufficient to accompany physiological retinal development and that minor developmental disturbances, which we cannot completely rule out, can be compensated over time. The fact that Irf8 -deficient microglia exhibit transcriptional changes that reduce their responsiveness while maintaining a normal retinal phenotype, provides an ideal setting to study the role of microglia in the development of choroidal neovascularisation, which is known to be associated with significant microglia activation and migration [ 35 , 52 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that Irf8 -deficient MG are functionally sufficient to accompany physiological retinal development and that minor developmental disturbances, which we cannot completely rule out, can be compensated over time. The fact that Irf8 -deficient microglia exhibit transcriptional changes that reduce their responsiveness while maintaining a normal retinal phenotype, provides an ideal setting to study the role of microglia in the development of choroidal neovascularisation, which is known to be associated with significant microglia activation and migration [ 35 , 52 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…During adulthood, rMG interact closely with synapses to maintain synaptic structure and electroretinal function and continuously scan the local environment for danger signals associated with injury or pathogens [ 56 ]. In response to tissue damage or infection, rMG rapidly attain an activated phenotype, migrate towards the site of injury and contribute to phagocytosis, inflammation and pathological events [ 4 , 52 , 59 ]. As such, activated microglia cells have been found in the subretinal space of patients with age-related macular degeneration (AMD) and in particular at sites of choroidal neovascularisation (CNV) in neovascular AMD [ 11 , 20 ] which is a common cause of irreversible blindness in the elderly [ 10 , 60 ].…”
Section: Introductionmentioning
confidence: 99%
“…Histological studies showed that choroidal neovascular membranes are composed of ECM components such as collagen, fibronectin, and laminin (Grossniklaus and Green 1998;Grossniklaus et al 1994;Hinton et al 1998a, b;Lopez et al 1996). Recent RNA sequencing analysis of human CNV membranes furthermore revealed increased COL6A1, COL3A1, SPP1, and SPARC expression in human CNV membranes compared to control tissue (Schlecht et al 2020). Furthermore, periostin, which is a ligand for several integrins and thus supports epithelial cell adhesion and migration, is an important ECM component in human MNV (Yoshida et al 2019) and has been discussed as a possible anti-fibrotic therapeutic target (Nakama et al 2015).…”
Section: Extracellular Matrixmentioning
confidence: 99%
“…3). Most recently, these investigations were complemented by RNA sequencing and in silico analyses of human CNV specimens, providing additional insight into the cellular composition (Schlecht et al 2020). Further evidence on the cellular mechanisms underlying CNV formation is based on experimental CNV models.…”
Section: Cellular Composition Of Neovascular Fibrosis In Namdmentioning
confidence: 99%
See 1 more Smart Citation